2019
DOI: 10.1016/j.ejmech.2018.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based exploration and pharmacological evaluation of N-substituted piperidin-4-yl-methanamine CXCR4 chemokine receptor antagonists

Abstract: Using the available structural information of the chemokine receptor CXCR4, we present hit finding and hit exploration studies that make use of virtual fragment screening, design, synthesis and structureactivity relationship (SAR) studies. Fragment 2 was identified as virtual screening hit and used as a starting point for the exploration of 31 N-substituted piperidin-4-yl-methanamine derivatives to investigate and improve the interactions with the CXCR4 binding site. Additionally, subtle structural ligand chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
(118 reference statements)
1
12
0
Order By: Relevance
“…4). Adlere et al (2019) showed that small structural ligand changes lead to distinct interactions with CXCR4 and CXCL12, supporting the study with three-dimensional quantitative SAR (3D-QSAR) and proposed binding models.…”
Section: Downloaded Fromsupporting
confidence: 76%
“…4). Adlere et al (2019) showed that small structural ligand changes lead to distinct interactions with CXCR4 and CXCL12, supporting the study with three-dimensional quantitative SAR (3D-QSAR) and proposed binding models.…”
Section: Downloaded Fromsupporting
confidence: 76%
“…1, 2, and 3A). The (partial) overlap explains the different levels of chemokine displacement that are observed in experiments using different small molecule (potentially allosteric) modulators (Adlere et al, 2019). Moreover, the orthosteric binding site is divided into a minor subpocket and a major subpocket (Fig.…”
Section: Chemokine Receptor Structuresmentioning
confidence: 99%
“…Analysis of key interactions in crystal structures offers a rationale for designing ligand modifications. To illustrate, a recent study focused on the IT1t-bound CXCR4 crystal structure as a baseline to identify new fragment hits and analyzed the crystal structure to rationally design a fragment growing strategy (Adlere et al, 2019). In this study, the identification of a highly hydrophobic hotspot in the binding site of the cocrystallized ligand was Lessons from Chemokine Receptor X-Ray Structures used to generate analogs with increased lipophilicity to target the hotspot.…”
Section: Applications Of Chemokine Receptor Crystal Structures For Momentioning
confidence: 99%
“…The resulting nucleotide fragment (sig.LgBiT) contained the sequences for the restriction enzyme KpnI upstream of the sig sequence and the restriction enzyme BamHI downstream of the linker. This was then ligated to the pcDNA3.1(+) plasmid containing the human CXCR4 receptor (described in Adlere et al, 2019 ), creating the fusion of sig.LgBiT, a Gly-Ser linker and CXCR4 with the methionine start signal removed.…”
Section: Methodsmentioning
confidence: 99%